MICELLAR SOLUBILIZATION OF POLYNUCLEAR AROMATIC-HYDROCARBONS IN COAL TAR-CONTAMINATED SOILS - YEOM, IT; GHOSH, MM; COX, CD; ROBINSON, KG (AMER CHEMICAL SOC, 1995)
Solubilization of PAHs from a coal tar-contaminated soil obtained from a manufactured gas plant (MGP) site was evaluated using nonionic polyoxyethylene surfactants at dosages greater than cmc. Up to 25% of Soxhlet-extractable PAHs could be solubilized at surfactant loadings of 0.3 g/g of soil in 16 days in completely stirred batch reactors. Longer periods were required to reach equilibrium at higher surfactant dosages. Raoult's law satisfactorily described the partitioning of constituent PAHs between the weathered coal tar and the micellar solution. An equilibrium model was developed to predict the solubilization of PAHs from coat tar-contaminated soils for given properties of the soil, surfactant, and component PAHs. The model predicted solubilization of constituent PAHs reasonably well at low surfactant dosages. At extremely high surfactant dosages, the model failed to reliably predict solubilization. Presumably, mass transfer limitations prevented attainment of equilibrium during the duration (380 h) of solubilization experiments.
Keywords: WATER; SURFACTANTS; MIXTURES